Development of Pop-Up Book Media on Islamic Religious Education Subjects for Elementary School Students - Baharuddin, Hesti; Marwiyah, St.; Sana, Sana (South Sulawesi Education Development (SSED), 2025)
This study examines the development of pop-up book learning media in Islamic religious education subjects grade VI SD Negeri 361 Bailing, West Bajo District, Luwu Regency, to find the results of the development of Pop up book learning media to find out the results of the validity test and the results of the practicality test. This research is a type of Research and Development (R&D) research with research planning procedures using the ADDIE model, including Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques used were observation, interviews, and questionnaires. The data analysis techniques used are product validity and learning media practicality analysis. The study results show that 1) The development of Pop-up book learning media is carried out systematically using the ADDIE model. 2) The Validity of Pop-up book learning media is assessed by media experts, with a percentage of 66.6%, and material experts, with a percentage of 93.7%, which is a very valid category. 3) The practicality of pop-up book learning media was based on the assessment of educators; the percentage was 94%, and the student's responses were 90% in the very practical category.